Burning Bright, Not Out! Therapist Well-Being in the Face of What We Face - Richardson/Kinewesquao, Cathy (Murmurations: Journal of Transformative Systemic Practice, 2023)
At a recent conference in Lyon, an American researcher declared that we are all traumatised, all of us including counsellors, clients, workers, lawyers, activists. I was taken aback thinking, “wait a moment!” I am not willing to believe that, in the face of struggle and adversity, we are all mentally ill. Counsellors/therapists form part of a community circle responding to violence, harm, betrayal, grief and heartbreak. We are often inspired by our clients, their survivance, their resistance and the ways they signal injustice. The academic presenter was likely influenced by theories of compassion fatigue and vicarious trauma - ideas that accuse our clients of hurting us. I wonder to what extent these theories hurt us or get us thinking in ways that are individualising and unhelpful.